(untitled) (International Scientific Journal Alfraganus, 2025)
This article examines the main issues of learning Spanish as a second language and discusses ways to address them. Spanish is one of the most widely spoken languages in the world, and learning it as a second language has become a widespread practice in many countries. Every year, many people start learning Spanish, especially due to the demands in the United States. However, teaching Spanish as a second language presents a number of current challenges.